Context sensitive transit oriented development assessment: AHP weighted TOD standards for regional railway hubs in Thailand - Chaiwat Sangsrichan; Patcharida Sungtrisearn; Nopadon Kronprasert; Auttawit Upayokin; Preda Pichayapan (Decision Science Letters)
This study develops a context-specific Transit-Oriented Development (TOD) evaluation framework for Thailand's regional railway hubs by integrating the Analytic Hierarchy Process (AHP) with established TOD Standards. Through expert-based pairwise comparisons, we determined that transit accessibility (19.1%), connectivity (15.0%), and walkability (14.1%) represent priority criteria for the Thai context, contrasting with the uniform weighting system of international standards. We applied this AHP-weighted framework to assess six regional railway stations: Chiang Mai, Phitsanulok, Nakhon Ratchasima, Khon Kaen, Pattaya, and Hat Yai Junction. Comparative analysis revealed that Hat Yai Junction achieved the highest TOD potential ranking under both standard (74/100) and AHP-weighted (79.7/100) methods, followed by Chiang Mai (72/100 standard; 78.8/100 weighted). The most notable scoring differential appeared in Nakhon Ratchasima (69/100 vs. 78.4/100), demonstrating the significant impact of context-sensitive weighting. All stations showed common weaknesses in cycling infrastructure (average 3.2/5) and car use reduction metrics while achieving the highest scores in transit accessibility criteria. Station-specific evaluation identified targeted improvement priorities: enhancing cycling networks in Chiang Mai, improving pedestrian infrastructure in Phitsanulok, and increasing block connectivity in Pattaya. This contextualized framework gives planners a practical tool for prioritizing TOD investments in Thailand's regional centers.